In-situ cured silicon-based composite negative pole piece as well as preparation method and application thereof

By applying polymer electrolyte precursor solution to the surface of the silicon-based negative electrode sheet and carrying out in-situ polymerization reaction, a silicon-based composite negative electrode sheet is formed, which solves the problems of volume expansion and dynamic interface evolution of the silicon-based negative electrode, and achieves higher cyclic stability and energy density.

CN119786530AActive Publication Date: 2025-04-08INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411982772.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The application of silicon-based anode in lithium-ion batteries faces the problems of solid electrolyte membrane rupture and active lithium loss caused by volume expansion, and the prior art is difficult to effectively solve the problem of dynamic evolution of the interface between silicon anode and electrolyte.

Method used

By applying a polymer electrolyte precursor solution to the surface of the silicon-based negative electrode sheet and performing in-situ polymerization reaction, a silicon-based composite negative electrode sheet with an in-situ polymer is formed. This method forms a uniform and dense polymer coating on the surface of the silicon-based negative electrode sheet, limiting volume expansion, enhancing adhesion, and forming a stable solid electrolyte interface.

Benefits of technology

It effectively limits the volume expansion of the silicon negative electrode, reduces the particle powdering and interface separation, significantly enhances the adhesion between active substance particles, ensures the structural integrity of the electrode sheet and the efficient transmission of ion and electrons, and improves the cycle stability and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786530A_ABST
    Figure CN119786530A_ABST
Patent Text Reader

Abstract

The invention relates to an in-situ cured silicon-based composite negative pole piece as well as a preparation method and application thereof. The silicon-based composite negative pole piece comprises a negative pole piece and a polymer electrolyte layer which is cured in situ and coats the surface of the negative pole piece; the polymer electrolyte layer is obtained through in-situ polymerization reaction of a precursor solution applied to the surface of the negative pole piece; the precursor solution contains a fluoroalkyl functional group; and the negative pole piece comprises a silicon-based material of which the surface is rich in hydroxyl. The composite negative pole piece disclosed by the invention not only can effectively limit the volume expansion of a silicon negative pole in a circulation process and reduce the phenomena of particle pulverization and interface separation, but also remarkably enhances the adhesive force among active substance particles, and ensures the structural integrity of the pole piece and the efficient transmission of ions and electrons. The silicon-based negative pole piece can form a stable solid-solid interface with the solid electrolyte through the polymer coating layer, so that the interface impedance is remarkably reduced, and the ion conduction efficiency is improved, thereby enhancing the cycling stability and safety performance of the battery while improving the energy density of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to an in-situ cured silicon-based composite negative electrode pole piece and a preparation method and application thereof. Background Art

[0002] At present, graphite and other materials are the main choices for commercial lithium-ion battery negative electrodes. However, alloy negative electrode materials with high specific energy (such as Si, Sn, P, etc.) have gradually attracted attention and started to be used due to their excellent specific capacity. Taking silicon-based negative electrodes as an example, Li 3.75 The lithium insertion capacity of Si is as high as 3580 mAh g -1 , and has a lower redox potential (0.2-0.4V vs Li + / Li) and lower cost, showing the potential to meet the demand for high-energy-density batteries.

[0003] However, during the alloying and dealloying process of silicon-based anodes, their volume changes can be as high as 300%, which raises a series of problems. On the one hand, this drastic volume change will cause the solid electrolyte membrane (SEI) layer to continuously rupture and reorganize, resulting in continuous loss of active lithium and shortening the cycle life of the whole battery; on the other hand, continuous stress may cause particle pulverization and binder failure, further deteriorating the cycle performance of silicon anodes. Although the volume expansion problem can be alleviated by nano-sizing of silicon, this method will significantly increase the cost and reduce the compaction density, thus limiting the commercial prospects of silicon-based anodes. In the prior art, by introducing carbon materials or LiSiO x Spatially confined materials have been proven to be an effective means of alleviating volume expansion. However, the dynamic evolution of the interface between silicon-based materials and electrolytes used as negative electrodes in liquid lithium-ion batteries has not been fundamentally solved. In summary, the application of high-silicon or pure silicon negative electrodes in liquid lithium-ion batteries still faces many challenges.

[0004] In contrast, due to the high mechanical hardness of inorganic solid electrolytes and the effect of external stacking pressure, the SEI generation and evolution mechanism of silicon anode in solid-state batteries is different from that in liquid lithium-ion batteries, which provides the possibility of achieving better cycle stability. Studies by Yi ng Shi rl ey Meng et al. have shown that the use of 99.9wt% micron silicon combined with sulfide solid electrolyte (Li6PS5Cl) can prepare all-solid-state batteries with high current density and high surface loading. The successful application of this micron silicon is due to the two-dimensional interface passivation effect between sulfide solid electrolyte and silicon, which effectively inhibits the continuous growth of SE I. However, in order to maintain the interface contact between silicon and silicon and silicon and electrolyte, all-solid-state batteries need to apply an external stacking pressure of 50-150MPa. Although increasing pressure can improve the performance of solid-state batteries to a certain extent, excessive stacking pressure has certain difficulties in practical applications. In addition, although many studies have reported the good performance of sulfide solid electrolytes when matched with silicon anodes, sulfide electrolyte membranes with a thickness of more than 1mm are usually used in experiments. When the thickness of the sulfide electrolyte membrane is reduced, problems such as increased difficulty in membrane preparation and dendrite penetration will occur, making it difficult for silicon anodes to achieve practical applications in high-energy-density batteries. Therefore, all-solid-state batteries that match silicon anodes with sulfide solid electrolytes still face many obstacles in the industrialization process.

[0005] In summary, the application of silicon anode in all-solid-state batteries still faces serious problems of interaction with solid electrolyte interfaces. Current solutions are difficult to fundamentally eliminate these problems and inevitably lead to a decrease in the electrochemical and mechanical properties of solid-state batteries. Therefore, there is an urgent need to improve solid-state lithium batteries with silicon-based anodes to solve key problems in practical applications. Summary of the invention

[0006] The purpose of the present invention is to provide an in-situ cured silicon-based composite negative electrode pole piece and its preparation method and application in view of the defects existing in the prior art. A silicon-based composite negative electrode pole piece with an in-situ polymer is obtained by applying a polymer electrolyte precursor solution on the surface of the negative electrode pole piece and performing an in-situ polymerization reaction. The silicon-based composite negative electrode pole piece forms a uniform and dense polymer coating layer on the surface of the silicon-based negative electrode pole piece, which can not only effectively limit the volume expansion of the silicon negative electrode during the cycle, reduce particle pulverization and interface separation, but also significantly enhance the adhesion between the active material particles, ensure the structural integrity of the pole piece and the efficient transmission of ions and electrons. At the same time, the silicon-based negative electrode pole piece can form a stable solid-solid interface with the solid electrolyte through the polymer coating layer, significantly reduce the interface impedance and improve the ion conduction efficiency, thereby improving the battery energy density while enhancing its cycle stability and safety performance.

[0007] To achieve the above objectives, in a first aspect, the present invention provides an in-situ cured silicon-based composite negative electrode plate, comprising:

[0008] A negative electrode sheet and a polymer electrolyte layer in-situ cured and coated on the surface of the negative electrode sheet; the polymer electrolyte layer covers at least 90% of the surface area of ​​the negative electrode sheet;

[0009] Wherein, the polymer electrolyte layer is obtained by in-situ polymerization reaction of a precursor solution applied to the surface of the negative electrode plate; the precursor solution contains fluoroalkyl functional groups; the negative electrode plate includes a silicon-based negative electrode material, and the surface of the silicon-based negative electrode material is rich in hydroxyl groups.

[0010] Preferably, the porosity inside the negative electrode plate is 10%-50%;

[0011] The in-situ cured silicon-based composite negative electrode plate further comprises: an in-situ cured polymer electrolyte located in the pores of the negative electrode plate, wherein the polymer electrolyte forms a through network inside the negative electrode plate;

[0012] The polymer electrolyte is obtained by in-situ polymerization of a precursor solution that penetrates into the pore structure of the negative electrode plate.

[0013] Preferably, it is characterized in that the precursor solution includes polymerizable monomers, and the polymerizable monomers include: carbonate, acrylate and fluoroalkyl acrylate in a volume ratio of (1-3):1:(1-3).

[0014] Further preferably, the polymerizable monomers include: vinylene carbonate, ethylene glycol dimethacrylate and perfluorooctyl ethyl acrylate in a volume ratio of (1-3):1:(1-3).

[0015] Preferably, the silicon-based negative electrode material includes: one or more of pure silicon, silicon-carbon compounds, lithium silicon compounds, lithium silicon-carbon compounds, silicon oxide compound materials, or a composite material of silicon and carbon, preferably a composite material of silicon and graphite, wherein the mass ratio of graphite to silicon is 0:100-90:10.

[0016] Preferably, the polymer electrolyte layer further includes an inorganic solid electrolyte, and the inorganic solid electrolyte includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

[0017] In a second aspect, an embodiment of the present invention provides a method for preparing the in-situ cured silicon-based composite negative electrode sheet according to the first aspect, characterized in that the preparation method comprises:

[0018] Prepare a silicon-based negative electrode plate; the surface of the silicon-based negative electrode material is rich in hydroxyl groups;

[0019] Preparing a precursor solution for in-situ curing to form a polymer electrolyte; the precursor solution contains a fluoroalkyl functional group;

[0020] The precursor solution of the in-situ curing polymer is applied to the surface of the silicon-based negative electrode plate, and after standing and soaking, the precursor solution is polymerized by light and / or heat to obtain the silicon-based composite negative electrode plate.

[0021] Preferably, the preparation of a precursor solution for in-situ curing to form a polymer electrolyte specifically comprises:

[0022] Carbonate, acrylate and fluoroalkyl acrylate are mixed in a volume ratio of (1-3):1:(1-3) to obtain a polymerizable monomer;

[0023] The polymerizable monomer is added to a clarified solution containing lithium salt in a mass ratio of 1:2-2:1, and after being mixed evenly, an initiator accounting for 0.05%-1% of the mass percentage of the entire precursor solution is added and mixed evenly to obtain the precursor solution.

[0024] Preferably, the silicon-based negative electrode material includes: one or more of pure silicon, silicon-carbon compounds, lithium silicon compounds, lithium silicon-carbon compounds, silicon oxide compound materials, or a composite material of silicon and carbon, preferably a composite material of silicon and graphite, wherein the mass ratio of graphite to silicon is 0:100-90:10.

[0025] In a third aspect, an embodiment of the present invention provides a lithium battery, comprising: a positive electrode, a solid electrolyte membrane, and the silicon-based composite negative electrode plate described in the first aspect above or the silicon-based composite negative electrode plate obtained by the preparation method described in the second aspect above.

[0026] The embodiments of the present invention provide an in-situ cured silicon-based composite negative electrode plate, a negative electrode plate, and an in-situ cured polymer electrolyte layer coated on the surface of the negative electrode plate, wherein the polymer electrolyte layer is obtained by in-situ polymerization of a precursor solution applied to the surface of the negative electrode plate; the precursor solution contains a fluoroalkyl functional group; the negative electrode plate includes a silicon-based negative electrode material, and the surface of the silicon-based negative electrode material is rich in hydroxyl groups. The hydroxyl functional groups on the surface of the silicon-based negative electrode material interact with the fluoroalkyl functional groups in the polymer monomer and obtain the silicon-based composite negative electrode plate through in-situ polymerization. The silicon-based composite negative electrode plate forms a uniform and dense polymer coating layer on the surface of the silicon-based negative electrode plate, which can not only effectively limit the volume expansion of the silicon negative electrode during the cycle, reduce particle pulverization and interface separation, but also significantly enhance the adhesion between the active material particles, ensuring the structural integrity of the plate and the efficient transmission of ions and electrons. At the same time, after the monomers are polymerized, a tight polymer wrapping layer is formed on the surface of the silicon-based negative electrode piece, which can ensure low mechanical stress between the silicon negative electrode and the polymer electrolyte membrane of the solid-state battery, forming a good solid-solid contact interface, significantly reducing the interface impedance and improving the ion conduction efficiency, thereby improving the battery energy density while enhancing its cycle stability and safety performance.

[0027] The present invention uses a polymer electrolyte to modify the silicon-based negative electrode to obtain excellent interface compatibility and mechanical elasticity. The polymer electrolyte layer can serve as a good interface layer to buffer the severe volume expansion of the silicon negative electrode during lithium insertion and extraction and improve interface contact. The introduction of the interface layer can coat the surface of the silicon negative electrode with a polymer layer with high ionic conductivity, improve the problem of poor intrinsic kinetics of the silicon negative electrode and improve the rate performance, so that the silicon-based composite negative electrode pole piece of the present invention can be applied to all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a cross-sectional scanning electron microscopy (SEM) image of the negative electrode sheet before the precursor solution is added dropwise in Example 1 of the present invention;

[0029] Figure 2 This is a cross-sectional SEM image of the composite negative electrode sheet after curing according to Example 1 of the present invention;

[0030] Figure 3 This is a surface SEM image of the negative electrode sheet before the precursor solution is added in Example 1 of the present invention;

[0031] Figure 4 This is a surface SEM image of the composite negative electrode sheet after curing according to Example 1 of the present invention;

[0032] Figure 5 This is a Fourier transform infrared spectroscopy (FTIR) analysis diagram of the monomers in the precursor solution of Example 1 of the present invention before and after polymerization;

[0033] Figure 6 The cycle performance test diagram of button batteries assembled in Examples 1-5 and Comparative Examples 1-2 of the present invention at 60°C;

[0034] Figure 7 This is a test chart of the rate discharge performance of button cells assembled in Example 1 of the present invention and Comparative Example 1 at 60°C. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0036] The embodiment of the present invention provides an in-situ cured silicon-based composite negative electrode plate, comprising: a negative electrode plate and a polymer electrolyte layer in-situ cured and coated on the surface of the negative electrode plate. The polymer electrolyte layer covers at least 90% of the surface area of ​​the negative electrode plate; preferably, covers 100% of the surface area.

[0037] The silicon-based negative electrode material of the present invention includes a silicon-based material or a composite material of silicon and carbon.

[0038] Silicon-based materials include one or more of pure silicon, silicon-carbon compounds, lithium-silicon compounds, lithium-silicon-carbon compounds, and silicon-oxygen compounds; lithium-silicon compounds include lithium-silicon alloys or compounds formed by carbon and silicon in any proportion, including but not limited to Li 3.75 Si, Li3Si, Li2Si and Li4Si; lithium silicon-carbon compounds include lithium silicon-carbon alloys or compounds formed by lithium, carbon and silicon in any proportion; silicon oxide compounds include silicon and silicon dioxide composite silicon oxide (SiO x ), but not limited to the above materials. Silicon-based composite materials can include composite materials of silicon and carbon. Silicon and carbon can be mixed together to form a composite material, or the surface of a silicon material can be coated with carbon to form a composite material, or a silicon material can be loaded on a carbon-based material, or nano-silicon (nano-silicon carbon) can be deposited in the pores of a carbon medium. The silicon and carbon mentioned above can be nanoparticles or tubular materials, such as carbon nanotubes. The composite material of silicon and carbon is preferably a composite material of silicon and graphite, in which the mass ratio of graphite to silicon in the composite material is 0:100-90:10, that is, the mass percentage of graphite is 0-90%, for example 0, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, but is not limited to the above values.

[0039] The surface of the silicon-based negative electrode material of the present invention is rich in hydroxyl groups, which is related to the chemical properties of silicon and the surface treatment process in the preparation of silicon-based materials. First, silicon materials easily form a surface oxide film in the air, that is, a silicon dioxide (SiO2) film, and silicon dioxide will undergo a hydrolysis reaction in water or a humid environment to generate surface hydroxyl groups (-OH). Secondly, in the existing preparation process, in order to enhance the compatibility of silicon-based materials with electrolytes, the silicon surface is usually activated, such as oxidizing acid treatment (for example, hydrogen peroxide and concentrated sulfuric acid are mixed in a volume ratio of 30:70 and boiled at 70°C for 30 minutes to 1 hour), alkaline washing or plasma treatment. These processes will further increase the hydroxyl content on the silicon surface. Hydroxyl-rich silicon-based negative electrode materials can form stronger interfacial bonds with polymerized monomers or other functional groups in the electrolyte through hydrogen bonds or chemical bonds.

[0040] The negative electrode sheet of the present invention can be obtained by using existing conventional processes, for example, silicon-based negative electrode materials, conductive carbon, and binders are mixed and homogenized in a certain mass ratio, evenly coated on the current collector, and dried to obtain the negative electrode sheet. During the drying process, the negative electrode sheet will have certain pores due to factors such as the volatilization of the binder. Therefore, the interior of the negative electrode sheet is a porous structure, and its porosity reaches 10%-50%, which can be any value within the above range, such as 10%, 20%, 30%, 40% and 50%, including but not limited to this.

[0041] The porosity can be adjusted by adjusting the raw material ratio (such as the ratio of silicon: conductive carbon: binder) during the preparation of the negative electrode, controlling the particle morphology and particle size distribution of the raw silicon, controlling the slurry preparation process (such as the speed and time of stirring and dispersing, and selecting a solvent with a volatilization rate), optimizing the coating and drying process, and adjusting the compaction density. The adjustment of the porosity is a common technical means in this field and will not be described in detail here.

[0042] The polymer electrolyte layer is obtained by in-situ polymerization of a precursor solution applied to the surface of the negative electrode plate; the precursor solution contains fluoroalkyl functional groups; the negative electrode plate includes a silicon-based negative electrode material, and the surface of the silicon-based negative electrode material is rich in hydroxyl groups.

[0043] Specifically, the precursor solution includes polymerizable monomers, and the polymerizable monomers include: carbonate, acrylate and fluoroalkyl acrylate in a volume ratio of (1-3):1:(1-3). In a preferred embodiment, a composite solution of vinylene carbonate, ethylene glycol dimethacrylate and perfluorooctyl ethyl acrylate in the above volume ratio is used as a polymerizable monomer. The above volume ratio includes but is not limited to 1:1:1, 1:1:2, 1:1:3, 2:1:1, 2:1:2, 2:1:3, 3:1:1, 3:1:2, 3:1:3. Fluoroalkyl acrylate contains fluoroalkyl groups, which interact with hydroxyl groups on the surface of silicon-based negative electrode materials to bond together. Fluoroalkyl acrylates such as perfluorooctyl ethyl acrylate have excellent chemical stability, high temperature resistance, corrosion resistance and chemical erosion resistance, and have good interfacial compatibility with silicon-based negative electrodes, so they are suitable for solid-state lithium batteries with silicon-based negative electrodes. However, perfluorooctyl ethyl acrylate polymers cannot resolve lithium salts, so they are difficult to improve ionic conductivity when used in polymer electrolytes. For this reason, the polymer monomer composite system of the present invention also includes carbonate substances, which have excellent ability to resolve lithium salts, and the addition of carbonate substances with appropriate content can effectively improve the ionic conductivity of polymer electrolytes. In order to improve the mechanical properties of polymer electrolytes, the present invention adds ethylene glycol dimethacrylate to the composite system of polymer monomers, which can be used as a cross-linking agent of the system, thereby achieving cross-linking between polymer monomers and forming a network cross-linked structure, thereby greatly improving the mechanical properties of polymer electrolytes. The present invention controls the volume ratio of carbonate, acrylate and fluoroalkyl acrylate within the range of (1-3):1:(1-3), which can synergistically exert their respective effects, namely, form a good interface contact with the silicon negative electrode and improve the ion transmission conduction and mechanical properties of the polymer electrolyte.

[0044] When the precursor solution of the polymer electrolyte is applied to the surface of the negative electrode plate, the polymerized monomer can also penetrate into the porous structure inside the negative electrode plate, thereby fully filling the inside of the negative electrode plate. The polymer electrolyte obtained by the in-situ polymerization reaction of the polymerized monomer in the porous structure inside the negative electrode plate can form a strong bond with the silicon negative electrode particles, and can fully block the volume expansion of the silicon negative electrode during battery operation. The polymer electrolyte filled in the porous structure can construct a multi-dimensional mesh transmission channel for lithium ion transmission, thereby improving the transmission and diffusion capacity of lithium ions.

[0045] The monomers in the precursor solution of the present invention can fill the above pores, so that the particles are bonded together through the polymer electrolyte to form internal through-channels. Therefore, the composite negative electrode plate also includes a polymer electrolyte located in the pores of the negative electrode plate, and the polymer electrolyte forms a network of through-channels inside the negative electrode plate.

[0046] The precursor solution may contain, in addition to the above-mentioned polymerizable monomers, a lithium salt, an initiator and additives.

[0047] The lithium salt is one or more of an inorganic lithium salt and an organic lithium salt, including one or more of Li PF6, LiBF4, LiClO4, LiAsF6, LiBOB, Li TFSI, LiDFOB, and LiFSI.

[0048] The initiator is a substance that initiates the polymerization of the polymerization monomers, including but not limited to free radical initiators such as azobisisobutyronitrile (AIBN) and 2-hydroxy-2-methyl-1-phenylacetone.

[0049] The additives may be components of additives commonly used in the art, such as substances added to improve high and low temperature performance, mechanical properties, stability, conductivity, etc. Those skilled in the art may select specific additives and the amounts of the above components according to actual needs by following common technical means in the industry.

[0050] The polymer electrolyte of the present invention also includes an inorganic solid electrolyte, which includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte, and a halide solid electrolyte. The inorganic solid electrolyte can be added to the precursor solution by mixing, and the organic-inorganic composite solid electrolyte finally formed can improve the mechanical properties and ion conductivity of the electrolyte.

[0051] In summary, the polymer electrolyte on the in-situ cured silicon-based composite negative electrode plate of the present invention includes not only the polymer electrolyte layer coated on the surface, but also the polymer electrolyte filled in the porous structure.

[0052] The silicon-based composite negative electrode plate of the present invention has more than 90% of its surface, preferably 90%, 95%, 96%, 98%, 100% of its surface covered by an in-situ generated polymer electrolyte layer. The polymer electrolyte layer forms a protective layer on the surface of the negative electrode plate, and can form a good solid-solid contact interface with the solid electrolyte membrane of the solid-state battery, which is not only conducive to the diffusion and transmission of lithium ions, but also can greatly reduce mechanical stress.

[0053] The above describes the structure and basic properties of the in-situ cured silicon-based composite negative electrode plate of the present invention. Next, its preparation method is described.

[0054] The in-situ cured silicon-based composite negative electrode plate of the present invention can be prepared by the following steps.

[0055] Step 1, preparing a silicon-based negative electrode plate;

[0056] The silicon-based negative electrode plate of the present invention can be purchased from the market or prepared by itself. The silicon-based negative electrode plate used in the specific embodiment of the present invention was purchased from Liyang Tianmu Pioneer Battery Materials Co., Ltd.

[0057] The material surface of the silicon-based negative electrode can be appropriately activated as needed, such as oxidizing acid treatment (for example, hydrogen peroxide and concentrated sulfuric acid are mixed in a volume ratio of 30:70 and boiled at 70°C for 30 minutes to 1 hour), alkaline washing or plasma treatment to further increase the hydroxyl content on the silicon surface.

[0058] Step 2, preparing a precursor solution for in-situ curing to form a polymer electrolyte;

[0059] Specifically, carbonate, acrylate and fluoroalkyl acrylate are mixed in a volume ratio of (1-3):1:(1-3) to obtain a polymerization monomer; in a preferred embodiment of the present invention, vinylene carbonate, ethylene glycol dimethacrylate and perfluorooctyl ethyl acrylate are mixed in proportion to obtain a polymerization monomer.

[0060] The polymer monomer is added to the clarified solution containing lithium salt in a mass ratio of 1:2-2:1 of the polymer monomer:lithium salt, and after being mixed evenly, an initiator accounting for 0.05%-1% of the mass percentage of the entire precursor solution is added and mixed evenly to obtain a precursor solution of a polymer electrolyte.

[0061] The lithium salt in the precursor solution can be one or more of inorganic lithium salts and organic lithium salts, for example, one or more of LiPF6, LiBF4, LiC lO4, LiAsF6, LiBOB, LiTFSI, LiDFOB, and LiFSI; the mass ratio of the polymer monomer to the lithium salt is 1:2-2:1, and can be any value within the above range, for example, 1:1, 1:1.5, 1:2, 1.5:1, and 2:1.

[0062] In clear solutions containing lithium salts, the solvent may include:

[0063] The initiator is a substance that initiates the polymerization of the polymerization monomer, including but not limited to free radical initiators such as azobisisobutyronitrile (AIBN) and 2-hydroxy-2-methyl-1-phenylacetone. The mass percentage of the initiator in the precursor solution is preferably 0.05%-1%. It can be any value within the above range, such as 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%.

[0064] Step 3, applying the precursor solution of the in-situ curing polymer to the surface of the silicon-based negative electrode plate, allowing it to stand and soak, and initiating polymerization of the precursor solution by light and / or heat to obtain a silicon-based composite negative electrode plate.

[0065] The heat-induced heating temperature of the present invention is 50-100°C, and the heating time is 30 minutes to 48 hours. The heating temperature can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C; the heating time can be 30 minutes, 1 hour, 5 hours, 10 hours, 15 hours, 20 hours, 24 hours, 30 hours, 48 ​​hours, etc.

[0066] The light initiation of the present invention can be performed by using an ultraviolet lamp with a certain wavelength to initiate in-situ curing. For example, an ultraviolet lamp with a wavelength of 365nm is used for curing for 30 minutes to prepare an in-situ cured composite positive electrode plate.

[0067] The in-situ cured silicon-based composite negative electrode plate of the present invention can be used for polymer batteries, has high energy density, structural stability and excellent cycle performance, can be applied to lithium batteries, lithium battery packs or lithium battery modules, and is widely used in consumer electronics, electric vehicles, large-scale energy storage and other fields, and it also has good application prospects in large-scale energy storage systems.

[0068] The preparation method of the present invention adopts a method in which a precursor solution is placed on the surface of the negative electrode and then light and / or heat are initiated, so that the polymer monomer not only covers the surface of the negative electrode plate, but also penetrates into the pores of the negative electrode plate, and after in-situ polymerization and curing, a through network channel is constructed inside the negative electrode plate, thereby not only fully suppressing the volume expansion of the silicon negative electrode, but also greatly improving the transmission and diffusion capacity of lithium ions. The silicon-based negative electrode matching polymer electrolyte in the present invention has good thermal stability, which can effectively ensure the high-temperature cycle performance of the solid-state battery, and can also avoid thermal runaway behavior under battery abuse.

[0069] The preparation method of the present invention can construct a polymer electrolyte layer on the surface of the silicon negative electrode through in-situ curing technology, can achieve good matching between the silicon negative electrode and the polymer electrolyte, improve the battery cycle stability, and significantly increase the overall energy density of the battery.

[0070] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0071] The reagents, positive electrode materials, negative electrode materials, polymer monomers, lithium salts, additives, organic solvents, etc. used in the following examples and comparative examples are all conventional reagent products purchased from the market or prepared by the methods provided in the examples. If no specific experimental steps or conditions are specified in the examples, the operations or conditions of conventional experimental steps in the art are followed.

[0072] Example 1

[0073] (I) Preparation of precursor solution:

[0074] Weigh 500 mg of succinonitrile (SN), 460 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB), mix the three substances, and heat at 60°C for 2 h to obtain a clear solution;

[0075] The polymer monomers vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) were mixed at a ratio of 300uL: 100uL: 100uL and added to the clear solution, and 2mg of initiator azobisisobutyronitrile (AI BN) was added to obtain a mixture;

[0076] The mixture was stirred for 1 h to be uniformly mixed, thereby obtaining a precursor solution.

[0077] (II) Curing of negative electrode sheet:

[0078] Silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, the negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 1.2 mAh / cm 2 .

[0079] Use a pipette to transfer 20uL of the precursor solution in step (i) and drop it onto the silicon negative electrode plate. Then heat the plate in a high-temperature oven at 60°C for 24h, so that the precursor solution undergoes polymerization and forms a polymer electrolyte layer on the surface of the negative electrode plate.

[0080] (III) Assembling batteries:

[0081] Assembly of silicon anode half-cell:

[0082] The negative electrode sheet is used as the working electrode, the metal lithium sheet is used as the counter electrode, the PEO polymer solid electrolyte is selected as the diaphragm, and the CR2032 button battery shell is used for button battery assembly.

[0083] Example 2

[0084] (I) Preparation of precursor solution:

[0085] Weigh 500 mg of succinonitrile (SN), 460 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB), mix the three substances, and heat at 60°C for 2 h to obtain a clear solution;

[0086] The polymer monomers vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) were mixed at a ratio of 100uL: 100uL: 300uL and added to the clear solution, and 2mg of initiator azobisisobutyronitrile (AI BN) was added to obtain a mixture;

[0087] The mixture was stirred for 1 h to be uniformly mixed, thereby obtaining a precursor solution.

[0088] (ii) curing of the negative electrode sheet and (iii) assembling the battery, the specific methods are the same as those in Example 1.

[0089] Example 3

[0090] (I) Preparation of precursor solution: The specific method is the same as that in Example 1.

[0091] (II) Curing of negative electrode sheet:

[0092] Silicon-carbon composite material (graphite: silicon = 90:10, mass ratio): conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) was mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, a negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 1.2 mAh / cm 2 .

[0093] Use a pipette to transfer 20uL of the precursor solution in step (i) and drop it onto the silicon-carbon composite negative electrode plate, then heat the plate in a high-temperature oven at 60°C for 24h, so that the precursor solution undergoes polymerization and forms a polymer electrolyte layer on the surface of the negative electrode plate.

[0094] (III) Assembling the battery: The specific method is the same as that in Example 1.

[0095] Example 4

[0096] (I) Preparation of precursor solution:

[0097] Weigh 500 mg of succinonitrile (SN), 460 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB), mix the three substances, and heat at 60°C for 2 h to obtain a clear solution;

[0098] The polymer monomers vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) were mixed at a ratio of 300uL: 100uL: 100uL and added to the clear solution, and 2mg of initiator azobisisobutyronitrile (AI BN) was added to obtain a mixture;

[0099] The mixture was stirred for 1 hour to be evenly mixed, and 10 wt% of nano lithium lanthanum zirconium oxide LLZO solid electrolyte powder was added, and the mixture was stirred for 4 hours to be evenly mixed to obtain a precursor solution containing an inorganic solid electrolyte.

[0100] (ii) curing of the negative electrode sheet and (iii) assembling the battery, the specific methods are the same as those in Example 1.

[0101] Example 5

[0102] (I) Preparation of precursor solution:

[0103] Weigh 500 mg of succinonitrile (SN), 460 mg of lithium bis(fluorosulfonyl)imide (LiFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB), mix the three substances, and heat at 60°C for 2 h to obtain a clear solution;

[0104] The polymer monomers vinylene carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) were mixed at a ratio of 300uL: 100uL: 100uL and added to the clear solution, and 2mg of initiator azobisisobutyronitrile (AI BN) was added to obtain a mixture;

[0105] The mixture was stirred for 1 h to be uniformly mixed, thereby obtaining a precursor solution.

[0106] (ii) curing of the negative electrode sheet and (iii) assembling the battery, the specific methods are the same as those in Example 1.

[0107] Comparative Example 1

[0108] Silicon: conductive carbon (Super P): binder (carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 2:3) were mixed and homogenized in a mass ratio of 90:3:7, and evenly coated on copper foil. After drying, the negative electrode sheet was obtained, and the surface capacity of the electrode sheet was 1.2 mAh / cm 2 .

[0109] The negative electrode sheet is directly used as the working electrode to assemble a button cell with a metal lithium sheet and a PEO polymer film.

[0110] Comparative Example 2

[0111] (I) Preparation of precursor solution:

[0112] Weigh 500 mg of succinonitrile (SN), 460 mg of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and 60 mg of lithium difluorooxalatoborate (LiDFOB), mix the three substances, and heat at 60°C for 2 h to obtain a clear solution;

[0113] The polymerization monomers vinylene carbonate (VC) and ethylene glycol dimethacrylate (PEGDA) were mixed at a ratio of 400uL:100uL and added to the clear solution, and 2mg of initiator azobisisobutyronitrile (AI BN) was added to obtain a mixture;

[0114] The mixture was stirred for 1 hour to be uniformly mixed, thereby obtaining a precursor solution. The obtained polymer precursor solution does not contain a fluoroalkyl functional group.

[0115] (ii) curing of the negative electrode sheet and (iii) assembling the battery, the specific methods are the same as those in Example 1.

[0116] The performance of the materials and batteries obtained in the above embodiments and comparative examples was characterized.

[0117] Morphological characterization:

[0118] Figure 1 and Figure 2 They are cross-sectional scanning electron microscopy (SEM) images of the negative electrode sheet before the precursor solution is added in Example 1 and the negative electrode sheet after the precursor solution is added and solidified. Figure 3 and Figure 4 The following are surface scanning electron microscopy (SEM) images of the negative electrode sheet before the precursor solution is added in Example 1 and the negative electrode sheet after the precursor solution is added and solidified. Figure 1 and Figure 2 As shown in FIG. 1 , the polymerized electrolyte densely covers the negative electrode plate and penetrates into the pores of the plate, thereby obtaining a silicon negative electrode plate surface and pores with polymer electrolyte distributed therein. Figure 3 and Figure 4 As shown in the figure, the originally rough surface of silicon particles is evenly covered by a layer of polymer. This shows that the precursor solution can well infiltrate the electrode and achieve uniform polymerization, ensuring the ion passage and mechanical stability during the electrochemical process.

[0119] (II) Characterization of ingredients:

[0120] Figure 5 It is a Fourier transform infrared spectroscopy (FT IR) analysis diagram of the monomer in the precursor solution of Example 1 and after polymerization. Figure 5 (a), (b), (c) and (d) are the FT IR images of the electrolyte, PEGDA monomer, PFOEMA monomer and VC monomer after polymerization, respectively. Figure 3 It can be seen that Figure 5 1642 cm in (b) and (c) -1 The infrared absorption peak at Figure 5(a) The characteristic peak disappears, and the characteristic peak corresponds to the stretching vibration of the C=C bond of PEGDA and HFOEMA. The vibration peak disappears after polymerization, thus confirming the polymerization of PEGDA and HFOEMA monomers; Figure 5 (d) 3165cm -1 The infrared peak at comes from the stretching vibration of the =CH bond of vinylene carbonate (VC). Figure 5 The disappearance of (a) indicates VC polymerization. It can be seen that the peaks corresponding to the double bonds of each monomer disappear in the polymer solid electrolyte, indicating that the monomer polymerization is relatively complete.

[0121] (III) Electrochemical performance test:

[0122] Electrochemical tests were performed on each embodiment and comparative example:

[0123] 1) 0.2C cycle performance test at 60°C: The silicon negative electrode button half-cells in Examples 1-5 and Comparative Examples 1-2 were tested using a blue electric tester. The prepared half-cells were placed in a 60°C oven for charge and discharge tests. The voltage range was 5mV-1.5V, and 0.05C charge and discharge was activated for one cycle. Then, the charge and discharge were cycled at 0.2C constant current for 100 cycles to obtain the relevant data of the first discharge capacity, the 100th cycle discharge capacity, and the 100th cycle capacity retention rate, as shown in Table 1. The cycle performance test of the button cells assembled in Examples 1-5 and Comparative Examples 1-2 at 60°C is shown in the figure. Figure 6 shown.

[0124] Table 1 shows the test results of the in-situ polymerization and 30°C cycling performance of silicon negative electrode.

[0125]

[0126]

[0127] Examples 1-5 are in-situ cured silicon-based composite negative electrode plates of the present invention, the silicon-based negative electrode in Comparative Example 1 is not treated in any way, and the polymerized monomer in Comparative Example 2 does not contain a fluoroalkyl group. The assembled battery was subjected to a cycle performance test at 60°C.

[0128] The first discharge capacity of Example 1 at 0.05C is 2664.2mAh / g, the discharge capacity at 0.2C is 2251.2mAh / g, the discharge capacity after 100 cycles at 0.2C is 2166.0mAh / g, and the capacity retention rate is close to 96.2%. Compared with Example 1, the volume ratio of the polymerized monomers vinyl carbonate (VC), ethylene glycol dimethacrylate (PEGDA) and perfluorooctyl ethyl acrylate (PFOEMA) in Example 2 is adjusted from 3:1:1 to 1:1:3, and the first discharge capacity at 0.05C is 2397.3mAh / g, the discharge capacity at 0.2C is 2141.1mAh / g, the discharge capacity after 100 cycles at 0.2C is 1962.5mAh / g, and the capacity retention rate is close to 91.7%; compared with Example 1, the polymer electrolyte in Example 4 contains LATP solid electrolyte, which The first discharge capacity at 0.05C is 2490.7mAh / g, the discharge capacity at 0.2C is 2237.8mAh / g, the discharge capacity after 100 cycles at 0.2C is 1756.4mAh / g, and the capacity retention rate is close to 78.5%; compared with Example 1, the lithium salt in the polymer electrolyte in Example 5 is different, and its first discharge capacity at 0.05C is 2191.3mAh / g, the discharge capacity at 0.2C is 1982.2mAh / g, the discharge capacity after 100 cycles at 0.2C is 1485.3mAh / g, and the capacity retention rate is close to 74.9%. The capacity decay of Example 4 is faster because the solid electrolyte LLZO is difficult to be evenly distributed at the negative electrode interface, which is related to the dispersion process of the slurry, but the capacity of this embodiment is still higher than that of the comparative example. The capacity decay of Example 5 is due to the poor thermal stability of the lithium salt Li FS I. In order to ensure the softening of the PEO intermediate film, the battery was tested at 60°C, resulting in continuous deterioration of the interface, but the specific capacity of this example is also significantly higher than that of the comparative example. It can be seen that the silicon-based negative electrode lithium battery in Examples 1, 2, 4, and 5 has a high specific capacity and excellent cycle stability.

[0129] Compared with Example 1, a silicon-carbon composite negative electrode material is selected in Example 3, and its first discharge specific capacity at 0.05C is 764.8 mAh / g, the discharge specific capacity at 0.2C is 611.4 mAh / g, the discharge specific capacity after 100 cycles at 0.2C is 592.9 mAh / g, and the capacity retention rate is 97%, that is, it still has a high specific capacity after 100 cycles.

[0130] The silicon-based negative electrode of Comparative Example 1 has no in-situ polymerized electrolyte, and its first discharge capacity at 0.05C is 1684.8mAh / g, the discharge capacity at 0.2C is 1655.6mAh / g, the discharge capacity after 100 cycles at 0.2C is 1342.3mAh / g, and the capacity retention rate is 81%. It can be seen from the performance test results of Comparative Example 1 that even if PEO has softened at 60°C, the capacity is reduced because the electrolyte cannot fill the particles in the negative electrode plate, and the capacity increases slowly at the beginning of the cycle, indicating the existence of the interfacial activation process and the low capacity retention rate after the cycle. Compared with Comparative Example 1, the discharge capacity of Example 1 at 0.05C is increased by 979.4mAh / g, while the discharge capacity at 0.2C is increased by 595.6mAh / g, the discharge capacity after 100 cycles at 0.2C is increased by 823.7mAh / g, and the capacity retention rate after 100 cycles is increased by 15.2%. By comparison, it can be seen that compared with solid-state batteries assembled with conventional silicon-based negative electrodes, the present invention adopts an in-situ cured silicon-based composite negative electrode plate, and obtains a composite plate by in-situ polymerization of polymer monomers on the surface and inside of the silicon-based negative electrode. The composite plate has excellent discharge specific capacity and very good cycle stability, and still has excellent discharge specific capacity and capacity retention rate after long cycles.

[0131] The polyelectrolyte monomer in Comparative Example 2 does not contain fluoroalkyl functional groups. The first discharge specific capacity of Comparative Example 2 at 0.05C is 2413.7mAh / g, and the discharge specific capacity at 0.2C is 2400.7mAh / g, but the battery of Comparative Example 2 cannot be cycled for 100 weeks. The monomer in Comparative Example 2 does not contain fluoroalkyl functional groups, and the initial capacity is higher, but after about 20 weeks of cycling, the capacity decays rapidly, and the battery fails at about 80 weeks. Compared with Comparative Example 2, the discharge specific capacity of Example 1 at 0.05C is increased by 250.5mAh / g, and although the discharge specific capacity of Comparative Example 2 at 0.2C is higher, Comparative Example 2 cannot be cycled stably for a long time. By comparison, it can be seen that the monomer in Comparative Example 2 does not contain fluoroalkyl functional groups. Although it shows similar cycle stability in the early stage, after a short 20-week cycle, the discharge specific capacity drops, the battery fails at 80 weeks, and cannot be cycled to 100 weeks.

[0132] 2) Rate charge and discharge performance test at 60°C: The silicon negative electrode button half-cells in Example 1 and Comparative Example 1 were tested using a blue electric tester with a voltage range of 5mV-1.5V. The rate test selected the step settings of 0.02C, 0.05C, 0.1C, 0.2C, 0.5C, 1C, and 2C. Each step was cycled for 5 weeks, and then 0.1C was restored for cycling. Table 2 shows the discharge capacity of each step in the last week after the rate stabilized. The data related to the rate discharge capacity are as follows: Figure 7 shown.

[0133] Table 2 shows the test data of the 60℃ rate performance of silicon negative electrode solid-state batteries.

[0134] 0.02C 0.05C 0.1C 0.2C 0.5C 1C 2C 0.1C Example 1 2094.2 2071.7 2022.2 1991.2 1944.3 1871.7 1740.5 2033.2 Comparative Example 1 1960.0 1920.3 1911.1 1892.3 1855.8 1808.9 1619.1 1888.0

[0135] The solid-state lithium battery assembled with the in-situ cured silicon-based negative electrode composite pole piece of Example 1 and the half-cell of Comparative Example 1 directly selected the PEO film as the intermediate layer, and the two assembled batteries were subjected to rate performance testing at 60°C, including cycling the solid-state battery at 0.02C, 0.05C, 0.1C, 0.2C, 0.5C, 1C, and 2C, respectively, for 5 weeks, and then restoring to 0.1C for cycling. The discharge specific capacity of Example 1 at 0.02C is 2094.2 mAh / g, the discharge specific capacity at 0.05C is 2071.7 mAh / g, the discharge specific capacity at 0.1C is 2022.2 mAh / g, the discharge specific capacity at 0.2C is 1991.2 mAh / g, the discharge specific capacity at 0.5C is 1944.3 mAh / g, the discharge specific capacity at 1C is 1871.7 mAh / g, the discharge specific capacity at 2C is 1740.5 mAh / g, and the discharge specific capacity at 0.1C is 2033.2 mAh / g. The discharge capacity of Comparative Example 1 at 0.02C is 1960.0mAh / g, the discharge capacity at 0.05C is 1920.3mAh / g, the discharge capacity at 0.1C is 1911.1mAh / g, the discharge capacity at 0.2C is 1892.3mAh / g, the discharge capacity at 0.5C is 1855.8mAh / g, the discharge capacity at 1C is 1808.9mAh / g, the discharge capacity at 2C is 1619.1mAh / g, and the discharge capacity at 0.1C is 1888.0mAh / g. The capacity of Example 1 at each rate is higher than that of Comparative Example 1, and when it returns to the 0.1C cycle test, the capacity is higher and the cycle retention is better. It can be seen that the button cell assembled in Example 1 of the present invention exhibits excellent rate performance. Compared with Comparative Example 1, its discharge specific capacity at 0.02C, 0.05C, and 0.1C is higher than 100mAh / g, and the discharge specific capacity at 0.2C and 0.5C is higher than nearly 100mAh / g, the discharge specific capacity at 1C is higher than 62.8mAh / g, and the discharge specific capacity at 2C is higher than 121.4mAh / g. When it is restored to 0.1C, the discharge specific capacity is higher than 145.2mAh / g. By comparison, it can be seen that the present invention adopts a silicon-based negative electrode, having a polymer electrolyte layer located on the surface of the negative electrode pole piece, and the polymer electrolyte layer is obtained by in-situ polymerization of a precursor solution containing a fluoroalkyl group applied to the surface of the negative electrode pole piece, which has excellent rate performance and shows better electrochemical performance. The silicon-based solid pole piece obtained by in-situ polymerization of the present invention can ensure that the silicon negative electrode has excellent cycle stability and rate performance at 60°C.

[0136] The in-situ cured silicon-based composite negative electrode plate provided by the embodiment of the present invention comprises a negative electrode plate and a polymer electrolyte layer in-situ cured and coated on the surface of the negative electrode plate, wherein the polymer electrolyte layer is obtained by in-situ polymerization of a precursor solution applied to the surface of the negative electrode plate; the precursor solution contains a fluoroalkyl functional group; the negative electrode plate comprises a silicon-based negative electrode material, and the surface of the silicon-based negative electrode material is rich in hydroxyl groups. The hydroxyl functional groups on the surface of the silicon-based negative electrode material interact with the fluoroalkyl functional groups in the polymer monomer and obtain the silicon-based composite negative electrode plate through in-situ polymerization. The silicon-based composite negative electrode plate forms a uniform and dense polymer coating layer on the surface of the silicon-based negative electrode plate, which can not only effectively limit the volume expansion of the silicon negative electrode during the cycle, reduce particle pulverization and interface separation, but also significantly enhance the adhesion between the active material particles, ensuring the structural integrity of the plate and the efficient transmission of ions and electrons. At the same time, after the monomers are polymerized, a tight polymer wrapping layer is formed on the surface of the silicon-based negative electrode piece, which can ensure low mechanical stress between the silicon negative electrode and the polymer electrolyte membrane of the solid-state battery, forming a good solid-solid contact interface, significantly reducing the interface impedance and improving the ion conduction efficiency, thereby improving the battery energy density while enhancing its cycle stability and safety performance.

[0137] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An in-situ cured silicon-based composite negative electrode plate, characterized in that: The in-situ cured silicon-based composite negative electrode plate comprises: A negative electrode sheet and a polymer electrolyte layer in-situ cured and coated on the surface of the negative electrode sheet; the polymer electrolyte layer covers at least 90% of the surface area of ​​the negative electrode sheet; Wherein, the polymer electrolyte layer is obtained by in-situ polymerization reaction of a precursor solution applied to the surface of the negative electrode plate; the precursor solution contains fluoroalkyl functional groups; the negative electrode plate includes a silicon-based negative electrode material, and the surface of the silicon-based negative electrode material is rich in hydroxyl groups.

2. The in-situ cured silicon-based composite negative electrode plate according to claim 1, characterized in that: The porosity inside the negative electrode sheet is 10%-50%; The in-situ cured silicon-based composite negative electrode plate further comprises: an in-situ cured polymer electrolyte located in the pores of the negative electrode plate, wherein the polymer electrolyte forms a through network inside the negative electrode plate; The polymer electrolyte is obtained by in-situ polymerization of a precursor solution that penetrates into the pore structure of the negative electrode plate.

3. The in-situ cured silicon-based composite negative electrode plate according to claim 1, characterized in that: The precursor solution includes polymerizable monomers, and the polymerizable monomers include carbonate, acrylate and fluoroalkyl acrylate in a volume ratio of (1-3):1:(1-3).

4. The in-situ cured silicon-based composite negative electrode plate according to claim 3, characterized in that: The polymerizable monomers include vinylene carbonate, ethylene glycol dimethacrylate and perfluorooctyl ethyl acrylate in a volume ratio of (1-3):1:(1-3).

5. The in-situ cured silicon-based composite negative electrode plate according to claim 1, characterized in that: The silicon-based negative electrode material includes one or more of pure silicon, silicon-carbon compounds, lithium silicon compounds, lithium silicon-carbon compounds, silicon oxide compounds, or a composite material of silicon and carbon, preferably a composite material of silicon and graphite, wherein the mass ratio of graphite to silicon is 0:100-90:

10.

6. The in-situ cured silicon-based composite negative electrode plate according to claim 1, characterized in that: The polymer electrolyte layer also includes an inorganic solid electrolyte, which includes one or more of an oxide solid electrolyte, a sulfide solid electrolyte and a halide solid electrolyte.

7. A method for preparing an in-situ cured silicon-based composite negative electrode sheet according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Prepare a silicon-based negative electrode plate; the surface of the silicon-based negative electrode material is rich in hydroxyl groups; Preparing a precursor solution for in-situ curing to form a polymer electrolyte; the precursor solution contains a fluoroalkyl functional group; The precursor solution of the in-situ curing polymer is applied to the surface of the silicon-based negative electrode plate, and after standing and soaking, the precursor solution is polymerized by light and / or heat to obtain the silicon-based composite negative electrode plate.

8. The preparation method according to claim 7, characterized in that: The preparation of a precursor solution for in-situ curing to form a polymer electrolyte specifically includes: Carbonate, acrylate and fluoroalkyl acrylate are mixed in a volume ratio of (1-3):1:(1-3) to obtain a polymerizable monomer; The polymerizable monomer is added to a clarified solution containing lithium salt in a mass ratio of 1:2-2:1, and after being mixed evenly, an initiator accounting for 0.05%-1% of the mass percentage of the entire precursor solution is added and mixed evenly to obtain the precursor solution.

9. The preparation method according to claim 7, characterized in that: The silicon-based negative electrode material includes: one or more of pure silicon, silicon-carbon compounds, lithium silicon compounds, lithium silicon-carbon compounds, silicon oxide compounds, or a composite material of silicon and carbon, preferably a composite material of silicon and graphite, wherein the mass ratio of graphite to silicon is 0:100-90:

10.

10. A lithium battery, characterized in that: The lithium battery comprises: a positive electrode, a solid electrolyte separator and a silicon-based composite negative electrode plate as described in any one of claims 1 to 6 or a silicon-based composite negative electrode plate obtained by the preparation method as described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Novel negative electrode structure, preparation method thereof and battery

    CN114464766A

  • Electrode plate, preparation method thereof and lithium battery

    CN116111038A

  • Preparation method of polymer solid electrolyte, solid electrolyte and solid battery

    CN117229447A

  • Preparation method of all-solid-state lithium ion battery and all-solid-state lithium ion battery

    CN117239216A

Cited By

  • Electrode assembly with solid electrolyte, battery cell and manufacturing method

    CN121011709A

  • Secondary battery and preparation method thereof, energy storage system and electric equipment

    CN121076265A

  • Silicon negative electrode, preparation method thereof and sulfide solid-state battery

    CN122091503A